DISPOSITIFS DÉCLARÉS D’ENSEIGNEMENT DE LA LECTURE AU MOYEN DE LA LITTÉRATURE DE JEUNESSE EN CONTEXTE D’INCLUSION PÉDAGOGIQUE D’ÉLÈVES HDAA DU PREMIER CYCLE DU PRIMAIRE - Beaulieu, Judith; Marilyn, Dupuis-Brouillette; Bowen, François; Levasseur, Caroline; Montésinos-Gelet, Isabelle; Dupin de Saint-André, Marie (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2019)
Les recherches en lien avec l’enseignement avec la littérature de jeunesse auprès des élèves HDAA ont été réalisées en contexte de classes spéciales. Aucune d’entre elles ne s’intéressaient au contexte d’inclusion d’élèves HDAA dans des classes régulières, ni à décrire les liens entre, d’une part, le type et l’ampleur des dispositifs didactiques d’enseignement avec la littérature de jeunesse et, d’autre part, le nombre d’élèves HDAA inclus dans la classe. Il s’agit de l’objet de ce texte. Le devis est descriptif. Les résultats montrent des différences en fonction de la quantité d’élèves HDAA inclus.USE OF READING INSTRUCTION METHODS INCORPORATING CHILDREN’S LITERATURE IN INCLUSIVE EDUCATION CONTEXTS WITH ELEMENTARY CYCLE ONE HSMLD STUDENTSStudies on the use of children’s literature to teach students with handicaps, social maladjustments, or learning disabilities (HSMLD) have been conducted in the context of special education classes. Yet, none have explored the context of regular classrooms integrating students with HSMLD, nor described the links between the type and extent of pedagogical methods that incorporate children’s literature used to teach and the number of students with HSMLD included in the classroom. This article contributes to remedying this gap. Our methodological approach is descriptive. Results indicate differences in relation to the number of students with HSMLD included in the classroom.